Synthesis and Characterization of a Naphthalene-Derived Schiff Base for Fe³⁺ Sensing Applications - Kalyani Prakash Arote (International Journal of Cheminformatics, 2025)
The development of chemosensors for metal ions has gained significant attention due to their crucial role in industrial, environmental, and biological applications. Metal ion detection is essential for monitoring environmental pollution, industrial processes, and biological systems where metal homeostasis plays a vital role. In this study, we focus on the synthesis, characterization, and application of a novel naphthalene-based Schiff base ligand, derived from the condensation reaction between 1,8-diaminonaphthalene and 3-nitrobenzaldehyde. The ligand was synthesized using a simple and efficient synthetic approach and was subsequently characterized through spectroscopic techniques, including UV-Vis spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy. A key finding of this study is the ligand's high selectivity and sensitivity towards Fe³⁺ ions, which was confirmed through UV-Vis spectroscopic analysis. The Job’s plot analysis revealed a 1:1 binding stoichiometry between the ligand and Fe³⁺ ions, indicating strong coordination and potential application in metal ion sensing. The Schiff base ligand exhibits a distinct colorimetric response upon interaction with Fe³⁺, making it a promising candidate for visual detection methods. This work underscores the significance of Schiff base ligands in metallurgical and environmental applications, particularly in the selective detection of metal ions. The findings contribute to the advancement of chemosensor development for analytical and industrial purposes, highlighting their potential use in detecting and monitoring biologically and industrially relevant metal ions with high precision and efficiency.
Keywords: Fe³⁺ detection; Schiff base ligand; chemosensor development; metal ion sensing; naphthalene-based ligand